Investigating Trust In M-Wallets: Developing An Assessment Tool - Soukaina BOUALOU; Ilham EL HARAOUI (African Scientific Journal, 2023)
This article delves into trust issues concerning m-wallet adoption in Morocco. Given the pivotal role of m-wallets during the COVID-19 pandemic, exacerbated by lockdowns and social distancing measures, our study seeks to create a bespoke instrument to assess trust among Moroccan m-wallet users. Drawing from a comprehensive review of literature on trust within financial technologies and the applied methodology, our research aims to pinpoint factors that drive Moroccan consumers’ propensity to embrace m-wallets. Despite Morocco’s notable mobile connectivity and widespread internet usage, hurdles to financial inclusivity persist, leaving a considerable segment of the adult populace without banking access. In our endeavor, a survey involving 181 respondents was conducted, leading to the formulation of an enhanced four-item measurement scale. This scale aids stakeholders in devising strategies to bolster user trust, ultimately catalyzing broader m-wallet uptake. For the integrity of our trust indicators, an Exploratory Factor Analysis was performed. The results resonated well with recognized standards, reinforcing the validity of our findings.